Analisis Kemampuan Representasi Matematis Mahasiswa pada Teori Graph Ditinjau dari Karakteristik Cara Berpikir - Dwi Oktaviana; Abdillah Abdillah (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
Students abilities differ when given questions that require representing aspects to appear. This is because the ability of mathematical representation is influenced by the characteristics of the student way of thinking. The purpose of this study was to analyze the mathematical representation abilities of students in graph theory in terms of the characteristics of the way of thinking. This type of research uses qualitative research in the form of case studies. The research subjects were class B students in the sixth semester of IKIP PGRI Pontianak with one student taken for ways of thinking in Concrete Sequences (SK), Abstract Sequences (SA), Concrete Random (AK), and Abstract Random (AA) with selected using purposive sampling technique. The main instruments in this research is the researcher and the necessary supporting instruments include test questions on mathematical representation abilities, questionnaires on the characteristics of ways of thinking, and interview guidelines. To test the validity of the data used triangulation techniques. Data analysis was performed by data reduction, data presentation and conclusion. The results of the study showed that students with the SK and Sa way of thinking had fulfilled all the indicators of mathematical representation abilities, namely verbal, visual, and symbolic representations because their way of thinking was detailed and mastered the concept, while students with the AA and AK thinking only met the indicators of verbal representation due to the unstructured way of thinking and not mastering the concept.